Nursing informatics. Taking the 'I' road: from nursing informatician to CEO, CIO, or CFO. - Simpson RL (Nursing Administration Quarterly)
Strategically and fiscally, information technology (IT) has become one of the most significant areas in today's health care organizations. As clinical systems begin to constitute the lion's share of IT budgets, the progression from nurse information to 'C' level should be an increasingly logical one. But is it? This article addresses why and how nurses can move up the administrative ladder and the value of technological expertise to that advancement. Copyright © 2001 by Aspen Publishers, Inc.